The Role of the Sunan Drajat Lamongan Islamic Boarding School Education System in Improving the Life Skills of Santri - Setiawan, Muhammad Febri; Asrori, Muhammad David; Ainurrofiq, Muhammad Reza; Febriansyah, Diqki Dias (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2023)
The aims of this study were: (1) to explain the education system at the Sunan Drajat Islamic boarding school. (2) to explain the life skills possessed by students at the Sunan Drajat Islamic Boarding School. (3) to explain the role of the Islamic boarding school education system in improving the life skills of students at the Sunan Drajat Islamic boarding school. In this study, researchers used a qualitative descriptive method with a case study approach—data collection techniques using interviews, observation, and documentation. The data analysis used is data reduction, data presentation, and data verification. From the results of this study, it can be seen that the Islamic boarding school education system plays a full role in improving the life skills of students at the Sunan Drajat Islamic boarding school. Examples of life skills development at the Sunan Drajat Islamic boarding school are personal skills development in the form of worship coaching, social skills development in the form of Javanese krama inggil language habituation, academic skills development in the form of reciting activities and formal schools, vocational skills development in the form of agriculture, trade, carpentry, animal husbandry, banking and the arts. This is done so that students can develop and hone their skills in Islamic boarding schools in accordance with their interests and talents as provisions for independent living when they enter society later